Pendekatan Jaringan Sosial untuk Menganalisis Partisipasi Politik di Indonesia di Masa Pandemi Covid-19: Scoping Review - Tery Setiawan; Muhammad A.S. Hikam; Antonius Suhartomo; Sefty Meliana Tamba; Elkana William Hasibuan; Azzizah Mulia Kusumaningrini Kartodirdjo; Syafira Fauzia; Thariq Auliya Arrazaq (Universitas Kristen Maranatha, 2022)
This study is intended to conduct a scoping review of the application of social network analysis (SNA) in predicting political participation in Indonesia, especially during the Covid-19 pandemic. The literature shows that investigations into political participation are not new in Indonesia. However, research that uses the application of SNA as an approach to explain the behavior of political participation in Indonesia is still very rare. For this reason, a scoping review is needed to provide an overview of political participation using a social network lens. The scoping review implementation was guided by Arksey and O'Malley's 5-step framework. The results of the scoping review show that the political participation among Indonesians is considered at a sufficient level, especially at the regional level. However, investigations of political participation using the SNA method are shown to be very rare. This research is useful for showing topics that can be explored in the social and political fields, especially by using the individual social network approach.